Effect of lysozyme based Opuntia ficus-indica mucilage edible coating on shelf life of papaya (Carica papaya L.) fruits - Yadav, Durva; Dagadkhair, Amol; Shere, Prerna; Patil, Vaibhav (Journal of Postharvest Technology, 2023)
Papaya is a highly perishable fruit with a very short postharvest life due to its susceptibility to mechanical injury, physiological disorders, and infection caused by several pathogens that can rapidly reduce fruit quality. The current investigation aims to assess the impact of Opuntia ficus indica mucilage combined with lysozyme applied as edible coating on papaya fruit quality, sensory indices, and microbiological characteristics during storage at RT. Opuntia ficus-indica fruit polysaccharide was utilised as a component of an edible coating. The five edible antimicrobial coating formulations were created using lysozyme in varied concentrations: 0 (control), 0.2 (T1), 0.4 (T2), 0.6 (T3), 0.8 (T4), and 1 % (T5). The antimicrobial edible coated samples were subjected to sensory, chemical, and microbial evaluation and T5 sample showed higher overall acceptability. The uncoated papaya showed a significantly greater linear rise in weight loss after storage at RT than the coated papaya. The T5 sample was effective in maintaining fruit weight, TSS, pH, and acidity. The lysozyme-mucilage based coating had positive effect on reducing the S. aureus on papaya surface. Therefore, it is concluded that developed antimicrobial edible coating has a potential to reduce microbial load while keeping sensorial qualities and hence could be commercialized.